Lithuanians and polish resistance movements in 1942–1945: connections and differences - Bubnys, Arūnas (Genocidas ir rezistencija, 2003)
The Soviet occupation of Lithuania in 1944 created the preconditions for cooperation between the Lithuanian and Polish underground. The Soviet government appointed mainly people of Slavic origin to local government bodies in eastern Lithuania. There were hardly any Lithuanian civil servants in smaller towns, so there were no conditions for confrontation and tensions between Lithuanians and Poles. The NKVD–NKGB immediately launched brutal repressions against Polish and Lithuanian resistance members. This encouraged Lithuanians and Poles in the mixed districts to join ranks against the Soviet invaders and the Soviet rule activists. In 1944–1945, a few cases of cooperation between Lithuanians and Poles were recorded, but these were isolated events of no major significance. By the end of 1945, the Soviet repressive organs had virtually crushed the Polish armed resistance in Lithuania and the Lithuanian resistance was left ‘all on its own’. Some Polish men joined Lithuanian partisan units. However, favourable conditions for joint anti–Soviet resistance were not used to the fullest potential.
Keywords: German occupation; Lithuania; Poland; antisoviet resistance; antinazi resistance